CARA IBU MENGATASI KESULITAN MAKAN PADA ANAK PRA SEKOLAH DI DESA PENYENGAT OLAK KABUPATEN MUARO JAMBI TAHUN 2015 - Afridawaty MJ (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Preschool children was the children who aged 3 to 5 years. The Groth and development of pre school children was  influenced by the nutrition, activity, sleeping problem, dental health, prevention of an injury, and the parenting style.The nature of typical development influence children’s eating patterns such as  a child being too picky. Difficulty  eating is when a child is unwilling or refuses to eat with the type or amount of physiologicalage  appropriate. The pre school age children who have difficulty eating and can further  lead to complication a and impaired child development, so we need  a way to overcome  adversity  mother eating in children.The aimed of study  was to determine the description how mothers cope with eating problem in pre school children in Penyengat Olak Village Muaro Jambi. This study was a quantitative descriptive. The sampling technique was simple random sampling wit 38 Persons were being the sample. The result  showed from 38 respondent, 21 respondent (55,2%) less well in dealing with eating problem in children. Difficulty eating in children ia an important issue for older people, if not treated early. It is  expected the parents, especially  the mother can detect the caused difficulty eatingin children so  that treatment can be done quickly and accurately, and the parent were suggested applied the appropriate  parenting style for the preschool children to maximize the aptitude. Key word : Difficulty eating, mothers, pre school children